Analisis Buku Ummul Mukminin Aisyah R.A. dan Relevansinya terhadap Peran Muslimah dalam Perkembangan IPTEK - Mutia Oriza Sativa; Hidra Ariza (Lembaga Yasin AlSys, 2026)
Although women’s contributions to the development of Islamic civilization have been widely studied, research specifically analyzing the content of Sayyid Sulaiman An-Nadwi’s Ummul Mukminin Aisyah R.A. and its relevance to the role of Muslim women in the advancement of science and technology remains limited. This study aims to analyze the intellectual contributions of Aisyah R.A. as presented in the book and examine their relevance to strengthening the role of Muslim women in addressing developments in science and technology in the digital era. This study employed a qualitative approach with a library research design and a qualitative content analysis method. The primary data source was the book Ummul Mukminin Aisyah R.A., while the supporting data sources included various relevant scholarly works. Data were collected through documentation techniques and analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. The findings indicate that Aisyah R.A. made significant contributions to the development of the Islamic scholarly tradition through her roles as a hadith narrator, Islamic jurist, educator, and scholarly authority for the Companions. The intellectual values she exemplified, including a love of knowledge, critical thinking ability, integrity, and a commitment to disseminating knowledge, remain relevant to strengthening the capacities of Muslim women in the digital era. This study affirms that the intellectual example of Aisyah R.A. can serve as a conceptual foundation for developing Islamic Religious Education studies on the role of women in the Islamic scholarly tradition. The findings also have practical implications for educational institutions in integrating the example of Aisyah R.A. into efforts to strengthen the character, literacy, and competencies of Muslim women in addressing developments in science and technology, while opening opportunities for further research on the implementation of the intellectual values of Muslim female figures in the contexts of education and digital transformation.